2020
DOI: 10.1128/mra.00389-20
|View full text |Cite
|
Sign up to set email alerts
|

Three Draft Genome Sequences of Staphylococcus Species Isolated from the Urine of Healthy Bovine Heifers (Gyr Breed)

Abstract: Members of the Staphylococcus genus are known pathogens causing mastitis in dairy cows, which results in major economic losses. Here, we present Staphylococcus epidermidis UFMG-H7, Staphylococcus hominis UFMG-H7B, and Staphylococcus sciuri UFMG-H6, isolated from the urine of healthy purebred Gyr heifers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The human UT microbiota is the best studied UT microbiota amongst mammals. Isolation of strains from the bovine UT, including our prior work investigating other bacterial taxa ( Giannattasio-Ferraz et al, 2020a , b , c , d , e , 2021a ) and our study presented here, is a further step toward understanding the healthy bovine UT microbiota. Furthermore, here we have compared these bovine isolates to human UT isolates, producing the first examination of urinary bacteria and urinary phages from two different mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human UT microbiota is the best studied UT microbiota amongst mammals. Isolation of strains from the bovine UT, including our prior work investigating other bacterial taxa ( Giannattasio-Ferraz et al, 2020a , b , c , d , e , 2021a ) and our study presented here, is a further step toward understanding the healthy bovine UT microbiota. Furthermore, here we have compared these bovine isolates to human UT isolates, producing the first examination of urinary bacteria and urinary phages from two different mammals.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, microbiome studies have found bacteria within the UT of other healthy mammals, including canines ( Burton et al, 2017 ) and swine ( Torres Luque et al, 2020 ). Furthermore, through our prior efforts, we have isolated several different bacterial taxa from the UT of healthy cattle ( Giannattasio-Ferraz et al, 2020a , b , c , d , e , 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…So many reports are supporting the results of our study. Giannattasio-Ferraz et al [25] they also demonstrated that most superabundant phyla are rmicutes that contain 40-50% of the diversity followed by Proteobacteria, Bacteroides, and Actinobacteria in vaginal micro ora. Differences in bacterial diversity were observed between these studies because of Breed, Feed, environmental condition, geological location, age, etc.…”
Section: Discussionmentioning
confidence: 94%
“…The fact that C. phoceense has been primarily detected within the urinary tract of humans and now cattle suggests that this species may be specific to this environment. Recent studies have found that some of the same bacterial species inhabit both the bovine and human urinary microbiota [48,49]. Previous research found that the proteoglycan surface within the human and bovine bladder are similar [50]; in humans, this layer is a source for adhesion and nutrients by urinary bacteria [51].…”
Section: Discussionmentioning
confidence: 99%